2022
DOI: 10.3390/foods11213500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Screening of Commercialized Protein Supplements for Sports Practice

Abstract: Recent years have seen a rise in the popularity of the consumption of sports-related supplements. However, the hypothesis is raised that it is necessary to analyze the quality aspects of these supplements in relation to the information provided on the label, to avoid associated risks and obtain the greatest possible benefit from their consumption. Therefore, the aim of this study has been to carry out an analysis or screening of the protein supplements that are currently marketed in Spain. We analyzed the labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 67 publications
(142 reference statements)
1
14
0
Order By: Relevance
“…This study identified a high level of variation in the dominant nutrients between each sports food category, such as protein, fat, saturated fat, carbohydrate, and dietary fibre, as has been found by other analytical studies (22,40). This variation may be due to manufacturer determined serving size and recommended serves per day, as well as to the form of the product (e.g., powder, liquid, or bar).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This study identified a high level of variation in the dominant nutrients between each sports food category, such as protein, fat, saturated fat, carbohydrate, and dietary fibre, as has been found by other analytical studies (22,40). This variation may be due to manufacturer determined serving size and recommended serves per day, as well as to the form of the product (e.g., powder, liquid, or bar).…”
Section: Discussionsupporting
confidence: 78%
“…However, the sample was smaller than in the current audit, included only protein isolate products and examined protein quality, which was not a focus of the current study. Additionally, the European Union legislative framework has no specific regulations with reference to claims for sports foods and these are categorised as foodstuffs, therefore it is difficult to establish whether these foods do in fact meet the labelling requirements (22). Claims are important to consumers and influence choice, preference, and consumption (25,(48)(49)(50)(51)(52), and are sources of information that are easily processed by consumers via heuristics (53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding clearly indicates that, in addition to the aesthetics of the interface, clearly conveying the effects of payment and consumption amount to users is necessary. This will enhance user experience and satisfaction, reduce the risk of improper operation and help reduce the loss of users due to misleading consumption caused by poor design of apps [236,237]. H12 demonstrates that a user-friendly interactive interface can reduce consumers' confusion and frustration during use, and stimulate their curiosity.…”
Section: The Value Enhancement Role Of Ar Technology In Network Enter...mentioning
confidence: 99%